Error Analysis in Using Inflectional Morphemes Students’ Recount Text of English Students - Manihuruk, Leonita Maria Efipanias (IJECA (International Journal of Education and Curriculum Application), 2022)
Based on the explanation above, the researcher decides to conduct a research on inflectional morphemes errors in the recount text written by third semester students, this research is expected to identify of errors in using inflectional morphemes. So the researcher comes to the title “Error Analysis in Using Inflectional Morphemes Students’ Recount Text of English Students”. Based on definition above the researcher used a qualitative research because the researcher want to find out the types of errors in using inflectional morpheme in writing recount text of English students. The researcher taken one group of three groups of that English Department with consists of 30 students in a group. The study applied descriptive qualitative settled in collecting the case study that used to gain detail information concerning students’ error on inflectional morpheme in writing recount text. Based on the students writing recount text composition there are 106 errors. Based on the data, the writer classified the errors that occur into some categories as well: Addition, Omission, Misformation, and Misordering. The result of this research indicates that there are a number of errors made by third semester students of UHKBPNP English students in writing recount text using inflectional morpheme. Based on research finding, the researcher was concluded: “There are four types of errors commonly made by the students’ recount text using inflectional morpheme namely error of addition, omission, misformation, and misordering.